Segmenting visitors based on willingness to pay for recreational benefits: The case of Leiria National Forest - Oliveira, Fernanda (2019)
This article uses a criterion-based method to segment visitors in the context of a contingent valuation survey. The National Forest of Leiria, located in central Portugal, is used as case study. Respondents are assigned to segments through a chi-squared automatic interaction detector method according to their willingness to pay for recreational improvements. This method identifies the main socio-economic and behavioural variables that differentiate the segments. The results show that the segment with the largest willingness to pay is formed by visitors who contribute to environmental protection and rate their recreational experience in the forest as very good. Besides these environmentally friendly' visitors, two other segments show willingness to pay above average: graduates' and forest neighbours'. The study shows how the rich set of data provided by contingent valuation studies can be used to segment visitors, and therefore to support the planning and management of recreational facilities.